Scientific activity of students as a component of the educational process - Melnyk, Vira; Melnyk, Roman; Dekhtiarova, Olena; Upatova, Iryna; Boiko-Buzyl, Yuliia (My University, 2021)
The aim. To investigate the importance of the scientific component of the educational process of HEIs students and its basic elements. In this research were used theoretical and empirical levels, applied a closed-ended questionnaire aimed at the construction of thoughts about the scientific activity. The practical value of the study was to provide recommendations on how to improve the level of scientific training of students.
Scientific activity of students as a component of the educational process / V. Melnyk, R. Melnyk, O. Dekhtiarova, I. Upatova, Yu. Boiko-Buzyl // AD ALTA: Journal of Interdisciplinary Research, 2021. – Vol. 11. – Issue 2, Special Issue XXIV. – P. 68–71.
Keywords: ВНЗ, наукова робота, дослідження студентів, науково-освітня парадигма, наука в освітньому середовищі; HEIs, scientific work, students' research, scientific and educational paradigm, science in the educational environment; вузы, научная работа, студенческие исследования, научно-образовательная деятельность, парадигма, наука в образовательной среде